Farnesol modulation of Rhodotorula mucilaginosa in biofilm and planktonic forms - JARROS,ISABELE C. (2022)
Abstract Biofilms are important to the virulence of human pathogenic fungi, and some molecules have been found to play key roles in the growth and regulation of fungal biofilms. Farnesol, one of these molecules, is well-described for some microorganisms but is still scarcely known for Rhodotorula spp. This study aimed to evaluate the influence of farnesol on the biofilm of R. mucilaginosa. Initially, screening with 0.2 mM to 2.1 mM of farnesol was evaluated against planktonic forms. A concentration of this compound was then chosen and evaluated for its effect on biofilm in formation and on preformed biofilm after 24, 48 and 72 hours. The impact of farnesol was evaluated by colony-forming units (CFU) counts, determination of metabolic activity and quantification of total biomass. In the presence of 0.9 mM, farnesol was able to decrease the CFU number, at 48 hours, when the biofilm was in formation, although it did not affect the preformed biofilms. Thus, our results show that farnesol exerts a modulating activity during biofilm formation for R. mucilaginosa, with this compound reducing the metabolic activity and total biomass of the biofilms.